2017
DOI: 10.1016/j.jretconser.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of online and offline gender and goal directed shopping online

Abstract: The aim of this paper is to model the effect of the consumers' perceptions of their offline and online gendered behaviour on online utilitarian shopping motivation and purchase intentions. We propose that when consumers shop online their behaviour is mediated by two gendered behaviors; offline and online. Therefore, gender is defined by the environments effect on behaviour To test this proposition, five hundred and fifteen usable responses were collected in face-to-face interviews. The conceptual model was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 72 publications
1
19
0
1
Order By: Relevance
“…In-store characteristics like store layout, employee politeness, decor and music increased the level of consumers shopping experience (Triantafillidou et al, 2017). It was seen that consumers gathered shopping experience from the product reviews available online (Davis et al, 2017). While self-confidence was a personal value for hedonic shoppers on both channels, in-store shoppers felt that they had better control of shopping experience.…”
Section: Discussionmentioning
confidence: 99%
“…In-store characteristics like store layout, employee politeness, decor and music increased the level of consumers shopping experience (Triantafillidou et al, 2017). It was seen that consumers gathered shopping experience from the product reviews available online (Davis et al, 2017). While self-confidence was a personal value for hedonic shoppers on both channels, in-store shoppers felt that they had better control of shopping experience.…”
Section: Discussionmentioning
confidence: 99%
“…limiting physical contact (frequency and proximity) between people to reduce the risk of spread of a disease (CDC, 2020b). However, this comes with an adjustment of the population to new behavior with all of its consequences (Davis et al , 2017; Kim et al , 2008; Lee and Lee, 2020).…”
Section: Pandemics Disasters and Crisesmentioning
confidence: 99%
“…For instance, cost-saving and convenience oriented motivations drive shoppers to shop online, whereas socialisation and immediacy drive shoppers to visit physical stores (Boardman and McCormick, 2018). Previous research has demonstrated the influence of shopping motivation on different shopping channel settings, such as physical store (Yim et al, 2014;Rohm and Swaminathan, 2004), online (Davis et al, 2017;Ganesh et al, 2010), and mobile (Khajehzadeh et al, 2014;Yang and Kim, 2012). However, shoppers can seek value by combining the use of different shopping channels in a shopping trip as well.…”
Section: Shopping Motivationmentioning
confidence: 99%